Analysis of a proposal for using a film based on conceptual, procedural, and attitudinal content - Tavano, Lucas Henrique [UNESP]; Cortela, Beatriz Salemme Corrêa [UNESP] (Investigacoes em Ensino de Ciencias (IENCI), 2024)
This article explores the use of commercial films in the initial training of physics teachers, based on results from a research study that involved developing a teaching sequence centered on the film Radioactive (2019). It discusses the didactic possibilities of using a film to address conceptual, procedural, and attitudinal content through the presentation of proposals (based on initial planning) and, subsequently, research results to assess their feasibility. This is a case study with data collected from a group of pre-service physics teachers using a questionnaire with open-ended questions, analyzed using the Collective Subject Discourse method. Among the conceptual contents, the results indicated the possibility of exploring an analogy related to radioactivity, provided that appropriate procedures are used, such as identifying and comparing elements of the target situation and the analogy and encouraging discussions about positive and negative aspects. Regarding procedural contents, the study found the potential for developing content with varying levels of complexity and generality, related to the search, selection, comparison, interpretation, and analysis of information. Among the attitudinal contents, a finding is the potential for pre-service teachers to incorporate attitudes regarding their understanding of the didactic resource used, motivated by their positive perception of the experience during the activities, which could lead to similar practices in their professional performance.
ANÁLISE DE UMA PROPOSTA DE UTILIZAÇÃO DE UM FILME COM BASE NOS CONTEÚDOS CONCEITUAIS, PROCEDIMENTAIS E ATITUDINAIS
Keywords: Commercial film; Discourse of the Collective Subject; Initial training of Physics teachers; Teaching resource